"What is it that's going on there" – Jødedommen og Internettet - Lindeberg, Sahra (Nordisk judaistik, 1997)
The purpose of this article is to examine what happens to the message of religious groups when it is disseminated through the Internet, and whether we as students of religion can use well-known methods to study the religious groups on this new media. In order to look into this problem we have chosen to focus on two Jewish groups, namely Satmar-and Chabad-Chasidism. We attempt to show how the introduction by Erving Goffman of the concepts of "frames" and "situations" is particularly useful for our understanding of the interaction on a homepage, but has to be supplemented with Stuart Hall’s concept of hegemony, as Goffman isn’t concerned with the motivations of the groups’ introduction and maintenance of the "frames". Hall’s theory on the other hand shows that "frames" do not exist by themselves, but represent the ideological standings of the religious group. The application of the methods on the homepages of Satmar-and Chabad-Chasidism illustrates precisely that also on the Internet as well as in "real life" we find framing. Despite the fact that the visitor to the homepage gets the feeling navigating freely exactly the "frames" lead him to the perception of Judaism being in accordance with what the group holds for true Judaism, which for the Satmar-Chasidism is equivalent to anti-Zionism, and in the case of Chabad-Chasidism to messianism.